Effects of Toco phobia on Pregnancy Outcomes in Kirkuk City Hospitals - Najeeb Daood, Rusul; H. Khairi, Suhad (International Journal of Psychosocial Rehabilitation, 2020)
Background: Fear of childbirth interfering with the woman’s daily functioning is a severe form of tocophobia; there is increasing evidence that tocophobia has serious adverse effects on both mother and baby. Objectives: To determine the effects of tocophobia on pregnant women and newborns outcomes. Methods: A purposive sampling "nonprobability" consists of one hundred pregnant women who have signs and symptoms of tocophobia at the maternity department in hospitals in Kirkuk City in the third trimester of gestation age. The study was performed with the use of the scale of fear of childbirth (WDEQ-A) as well as a proprietary interview questionnaire and structured data documentation form by using both descriptive and inferential statistics. Results: The findings of the study show that all (100%) of the study sample are having prenatal and postnatal depression and insomnia; (89%) of them are requesting an elective cesarean section to avoid facing vaginal delivery; (78%) of them are not bonding early with their babies; (59%) of them are reporting a prolonged duration of labor. the newborn outcomes among pregnant women; shows that (76%) of them have a low birth weight child; all (100%) of the study sample are reported to have admitted their newborn for intensive care; (82%) reported poor breastfeeding. Conclusion: The study concludes that Tocophobia have negatively effect on maternal and newborn outcomes